Escaping the resource curse: does resource dependence reduction mitigate income inequality? - Zhijiu Yang; Mengxu Li (Humanities & Social Sciences Communications)
Abstract This paper quantifies the impact of resource dependence reduction on income inequality. Using an exogenous shock triggered by China’s sustainable program for resource-based regions and prefecture-level data during 2004–2020, we perform a difference-in-differences estimation and find that reducing resource dependence has a sizable narrowing effect on urban-rural income gap. On average, the sustainable program reduces the gap (as measured by a ratio indicator) by 4.11%, with the effect being more pronounced in regions with initial low institutional quality. Further evidence suggests that the rise of labor-intensive industries and the increased rural investment, which benefit the poor more, help explain the narrowing effect. This paper sheds light on the sustainable development of resource-dependent regions.